A new species of Tyrannomyrmex Fernández 2003 (Formicidae, Myrmicinae, Solenopsidini) from Western Ghats, Kerala, India - Sadasivan, Kalesh; Kripakaran, Manoj (Zootaxa, 2017)
A new species of Tyrannomyrmex (Hymenoptera, Formicidae), T. alii sp. nov., is described from the Western Ghats of Kerala State in southern India. This new species can be distinguished from other Tyrannomyrmex species using morphological characters, from T.dux by the petiolar shape, and from T. legatus and T.rex by surface sculpture and pilosity. The gyne of the genus is described for the first time. We provide detailed morphological descriptions of the gyne and worker castes, images from scanning electron microscopy, a key to all four known species of Tyrannomyrmex, and a note on the ecology of this rare genus.